Socio medical Difficulties of Strabismus In Childhood - Rashiti, Minevere; Zahiti, Kaltrina (Bangladesh Journal of Medical Science, 2017)
Strabismus congenital or aquired deviation of eye position may lead to severe psychosocial problems in childhood and puberty. Depression, interpersonal difficulties in relationships, abuse and mistreatment in school, work, sports and play and feelings of sadness as well as inferiority might be due to deviation of one or both eyes. Consequent ophthalmic examination are necessary to detect and treat strabismus to provide affected children a healthy and happy childhood. Bangladesh Journal of Medical Science Vol.16(2) 2017 p.194-195